La fortune critique d’une monnaie d’or : le coq gaulois de Jules-Clément Chaplain à l’épreuve de la presse (1895-1914) - Katia Schaal (Les Cahiers de l'École du Louvre)
Commissioned by the French government from Jules-Clément Chaplain in 1895 and put into circulation in 1899, the gold coin with the Gallic cockerel has given rise to a plethora of comments. A careful examination of the press of the time allows us to trace the conception, reception and use of the ten- and twenty-franc coins. An analysis of the publication rhythm and content of the articles provides information on the involvement of a new actor in the writing of the history of contemporary coins. The journalist, whether a simple chronicler or an ardent polemicist, appears successively to be an unwavering supporter of monetary reform, a witness to the long elaboration of symbols and then of the tools, and finally a judge and critic of the artistic and technical qualities of the object. Finally, the article reveals how, beyond the medal maker or minister’s will, this reform really captured the attention of the French.